Health behaviors and weight status among urban and rural children - Davis, AM (2008)
INTRODUCTION: Pediatric overweight is currently reaching epidemic proportions but little information exists on differences in weight related behaviors between urban and rural children. Objective: To assess health behaviors and weight status among urban and rural school-age children. METHODS: Fifth-grade children at two urban and two rural schools were invited to participate in an assessment study of their health behaviors and weight status. A total of 138 children (mean age = 10 years; % female = 54.6) chose to participate. RESULTS: Children in rural and urban areas consumed equivalent calories per day and calories from fat, but rural children ate more junk food and urban children were more likely to skip breakfast. Urban children engaged in more metabolic equivalent tasks and had slightly higher total sedentary activity than rural children. The BMI percentile was equivalent across rural and urban children but rural children were more often overweight and urban children were more often at risk for overweight. CONCLUSIONS: Although some variables were equivalent across urban and rural children, results indicate some key health behavior differences between groups. Results should be interpreted with caution as the sample size was small and there were demographic differences between urban and rural samples.